The Role Of Emotional Intelligence in The Board Of Directors and Its Impact On The Performance and Value Of Institutions and Conservative Practices In Light Of Crises (Applied Research On a Sample Of Banks Listed On ISX) - yassir nori Mohammed; Mustafa Abdalsamea Abdalhamed; Najlaa Tareq Kadhim (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to underscore the significance of women's emotional intelligence in enhancing the effectiveness of the Board of Directors, a crucial component of internal governance, particularly during crises. Despite strides made in recent decades in appointing women to senior roles in government, business, and education, challenges persist in improving women's leadership opportunities, especially in developing countries. The study utilizes statistical methods, including Pearson's correlation, to analyze the relationships between variables within a sample of banks listed on the Iraqi securities market, comparing periods before and during the COVID-19 pandemic (2019 and 2020). The goal is to measure the impact of female emotional intelligence on the Board of Directors' ability to manage crises, focusing on variables such as conservative accounting policies, Board compensation and benefits, meeting frequency, the ratio of external auditor fees to enterprise capital, enterprise capital, share profitability, and the market-to-share profitability ratio. Findings indicate that emotional intelligence (measured by the number of females on the Board) positively influences conservative accounting policies and meeting frequency during crisis periods. Conversely, the pre-crisis period showed a negative relationship, suggesting a proactive and risk-responsive stance by women during crisis. Additionally, the study observed an inverse relationship between crisis periods and both Board compensation and external auditor fee ratios, implying a cost-reduction strategy facilitated by female emotional intelligence. The crisis period also saw an increase in the profitability of individual shares and the market-to-share profitability ratio. The research recommends expanding the study to compare the role of emotional intelligence in Boards between developing and developed economies.